Indicators of disturbance and recovery of a tallgrass prairie ecosystem following military vehicle traffic - Shaw Althoff, Peggy S. (Kansas State University, 2007)
Range and Training Land Assessment (RTLA) and Land Rehabilitation and Maintenance (LRAM) are key components of The United States Army's Integrated Training Area Management (ITAM) Program, which outlines its commitment to support the sustainable use of military training lands. The primary purpose of the RTLA Program is to provide information and recommendations regarding the condition of training lands to range managers for scheduling of training areas and monitoring the effectiveness of rehabilitation projects. The goal of the LRAM component of ITAM is to reduce the long-term impacts of training on installations through the implementation of improvements to vegetation cover and repairs to landscape damage in disturbed areas. Fort Riley Military Installation, located in the largest remaining expanse of tallgrass prairie in the Flint Hills of northeastern Kansas, is a major training reservation, with seventy percent of its 40,434 ha used for mechanized maneuvers. A randomized complete block design composed of M1A1 tank traffic in a figure-eight pattern during wet and dry soil conditions was established in each of two soil types, a silty clay loam and a silt loam, and recovery of physical, chemical, and biological indicator variables was monitored from 2005 through 2007. In a second study, the effectiveness of LRAM procedures, including leveling, mulching, and reseeding, was evaluated following wheeled vehicle disturbance. The goals of this study were to identify disturbance indicators appropriate for assessing soil quality and, based on the status of these indicators, develop a method for modeling the stage and rate of ecological degradation and potential response to remediation. Disturbance increased significantly during wet compared to dry soil conditions, for increased traffic intensity, and for curve compared to straight-a-way areas in both soil types. The greatest impacts were on above and below ground community structure, providing an effective bioindicator of ecosystem health for military training land managers. Remediation of wheeled vehicle disturbance with leveling and mulching, but not reseeding, increased total vegetation production. The tallgrass prairie typically is considered to be among the most resilient of military training lands, but resiliency is dependent upon soil type and training conditions, and may require longer periods of recovery than previously thought.
Keywords: Military disturbance; Tallgrass prairie; Soil quality; Ecological indicators; Abrams M1A1; Compaction; Agriculture, Agronomy (0285); Agriculture, Range Management (0777); Applied Mechanics (0346)